MEDIA MASSA DAN WACANA PEMIKIRAN ISLAM: Analisis Surat Kabar Islam-Komunis di Minangkabau - Erman Erman; Aziza Meria; Sefri Doni; Lukamanul Hakim (Universitas Darussalam Gontor, 2020)
This article aims to analysis mass media and Islamic thought discourse, analysis of Islamic-communist newspapers in Minangkabau. The method used to look at the problem was a historical method with a series of scientific work processes that then succeed in uncovering some findings. First, the Islam-communist newspapers (Pemandangan Islam and Doenia Achirat) were a local mass media deliberately designed by the Islamist-communist group to socialize ideas of Marxism and Islam. Second, both newspapers rolled out several discourses of Islamic thought that included theology, sharia, unity and progress. All this discourse has received serious attention from Islamic scholars in the classical period.